Pengaruh Harga dan Merek Terhadap Keputusan Pembelian Sepeda Motor di Kabupaten Ende - Damianus Tola; Yosef Moan Banda; Muhammad Faisal Salhu (Ekspektasi: Jurnal Pendidikan Ekonomi, 2023)
This study aims to determine the effect of price and brand on motorcycle purchasing decisions. This research uses quantitative methods with questionnaire data collection techniques, observation and documentation where the questionnaire will be distributed to respondents who own motorbikes, 20 male respondents and 20 female respondents. The results of this study indicate that there is an influence of price and brand on motorcycle purchasing decisions in Ende Regency. This is evidenced by the results of the analysis which obtained an Fcount value of 81.236 with a significant value of 0.000 <0.05 and F table of 3.24 thus Fcount is greater than Ftable (81.236 > 3.24) and the R Square value is 0.857 or 85, 7% which means that the motorcycle buyer's decision variable is influenced by the price variable and the motorcycle brand.